Preference for and Tolerance of the Intensity of Exercise questionnaire: Brazilian Portuguese version - Smirmaul, Bruno Paula Caraça [UNESP]; Ekkekakis, Panteleimon; Teixeira, Inaian Pignatti [UNESP]; Nakamura, Priscila Missaki [UNESP]; Kokubun, Eduardo [UNESP] (Universidade Federal de Santa Catarina, 2015)
The aim of the present study was to adapt the Preference for and Tolerance of the Intensity of ExerciseQuestionnaire (PRETIE-Q) for the Brazilian population and to perform an initial psychometric evaluation. The study consisted of two phases: I) translation and back-translation and production of a Brazilian Portuguese version of the questionnaire; and II) psychometric evaluation and construct validation using cross-sectional correlations between Preference and Tolerance scores and physical activity variables. Ratings of semantic, idiomatic, cultural, and conceptual equivalence, as well as total content validity and degree of understanding were adequately high. Response rate was 100% and the average response time was less than 3:30 minutes (204 ± 62 s). Internal consistency coefficients were 0.91 and 0.82, while two-week test-retest reliability coefficients were 0.90 and 0.89 for Preference and Tolerance scales, respectively. Preference and Tolerance scales were significantly correlated with both self-reported intensity (r = 0.48 and r = 0.57, respectively) and frequency (r = 0.40 and r = 0.51, respectively) of habitual physical activity, as well as with the total Godin questionnaire score (r = 0.20 and r = 0.40, respectively) and frequency of strenuous exercise (r = 0.29 and r = 0.49, respectively). The Brazilian Portuguese version of PRETIE-Q retained the psychometric properties of the original, demonstrating adequate internal consistency, test-retest reliability, and cross-sectional correlations with physical activity variables among young adults.
Keywords: Exercise prescription; Individual differences; Motor activity; Psychometrics; Translation